Assessment of Acceptability of Veggie Patty (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
In the early 1880s, Fletcher Davis of Athens Greece opened up a lunch counter that served ground meat patty. It is a small flat piece of meat that is present inside a bun. However, at present, we tried and made an innovation of what Fletcher Davis made and improved to make it more nutritious by adding vegetables. This product is also similar to the original but has vegetables instead of meat. It is also easy to prepare and eat. This veggie patty canbe made from ingredients such as carrots, kincay, cucumber, and potatoes. It looks similar to a hamburger but is made of vegetables instead of raw meat and also tastes different types of vegetables. The veggie patty is one of the few classic combinations that lends itself well to new riffs and versions. The health benefits are low fat and calories, high fiber, prevents diseases, etc. We used a survey questionnaire and selected 60 participants, which included10 Home Economics (HE)teachers and 50 HE Strand students. It is a study component to serve as a direction in reaching a goal, which is to sell this product to help the customer to become more aware of this new vegan trend that best substitutes meat products or to promote or to be an instrument to gather information for future researchers as reference. Generally, the findings showed that the total composite weighted means were 3.69 in terms of taste, 4.1 in terms of aroma, 4.45 in terms of nutritional value, and 4.29 in terms of presentation. The total composite weighted mean was4.13, which had a verbal interpretation of strongly agree. Therefore, the teachers have a composite weighted mean of 3.55 in terms of taste, 3.9 in terms of aroma, 4.5 in terms of nutritional value, and 4.5 in terms of representation. The total composite weighted mean was4.31, which was interpreted as strongly agree. Hence, the difference is not significant. Our product has more nutritional benefits and it is tastier because of the ingredients than the original. The product already has a good presentation. The taste dressing has a good aroma that influences the taste. The product has nutrients, such as vitamins A, B, and C, which are good for the heart and aid weight loss.
Keywords: veggie patty